ALTERED SERUM ENZYMES AND BIOCHEMICAL LEVELS IN ARABIAN RACING CAMELS WITH BONE FRACTURES - N. S. Alshamsi; T. S. Ksiksi; S. S. Ashraf (Journal of Animal and Plant Sciences, 2015)
Analysis of blood serum enzymesis an important and routine diagnostic tool commonly used to assess the well-being and metabolic status of racing camels. Unfortunately there are no well defined gender-specific published reference ranges for serum enzymes for healthy, lame and fractured camels. In this study, we report baseline reference range values for Glucose, Alkaline phosphatase (ALP), Aspartate aminotransferase (AST), Lactate Dehydrogenase (LDH), Creatine Kinase (CK), Gamma-glutamyltransferase (GGT), Albumin (ALB), Creatinine, Blood Urea Nitrogen (BUN), Intact Parathyroid Hormone (N-PTH), Osteocalcin (OC), Undercarboxylated Osteocalcin (UCOC) and Total Iron binding capacity (TIBC) in healthy (n=60), lame (n=31) and bone-fractured (n=20) racing camels. In addition to documenting gender-specific reference ranges for various biochemical parameters, we report for the first time significant differences in these parameters between healthy, lame and bone-fractured camels.  Our results show that of the 15 parameters analyzed, 13 of the hematological parameters in females and 11 parameters in male camels showed significant differences between at least one of the groups – healthy vs. lame, lame vs. fractured, or healthy vs. fractured. In conclusion, the present study clearly shows that some serum enzymes and biochemical levels are altered in racing camels with bone impairment and fractures.
Keywords: Blood serum enzymes Racing camels Biochemical parameters Gender-specific reference ranges Bone fractures